Creativity in Lif - Rubí Barquero, José Alberto (2011)
In this paper, the author explains the following ideas: that creativity is not restricted to the sphere of art, as it is usually considered, since art is just an expression of creativity; that people do many things that require creativity; and that not even creativity is an attribute of humans, since, from certain critical levels, we may observe behaviors in living beings that involve different degrees of aesthetic cognition.